A novel liquid level sensor design using laser optics technology - Erdem, M.E.; Güneş, D. (My University, 2012)
New materials and technological developments in electronics and computers have changed all of the industries, as well as the world itself. These technological advancements have evolved automotive industry by redefining the concepts like: performance, efficiency, fuel consumption, driving dynamics, ergonomics etc. to a level far beyond expected. Oil level in an internal combustion engine today is estimated by use of ultrasonic sensor devices. In this paper, the development stages of a novel liquid level sensing device and the development strategy is presented in detail. Several prototypes of the proposed new sensor are developed and tested. Experimental results indicate that by using the laser optics technology, sensitivity ranges of 0.0266 Pa in air pressure and 0.0064 mm water height measurements may be achieved. © 2012 IFSA.
Keywords: Engine Oil; Laser Optics; Liquid Level Sensor; Sensor(S); Whispering Gallery Mode (Wgm); Air Pressures; Development Stages; Development Strategies; Driving Dynamics; Engine Oil; Liquid Level; Liquid Level Sensors; Oil Levels; Sensitivity Range; Technological Advancement; Technological Development; Water Heights; Atmospheric Pressure; Automotive İndustry; Ergonomics; Internal Combustion Engines; Laser Optics; Whispering Gallery Modes; Sensors